Union Catalogue of Malay Manuscripts in Malaysia - Mamat, Wan Ali @ Wan Yusoff Wan; Noor, Noor Hasrul Nizan Mohammad; Seman, Muhamad Sadry Abu; Razak, Sitti Munirah Abdul (2017)
In this paper, we elucidate the importance of developing a union catalogue of Malay Manuscripts in Malaysia. Currently, all Malay manuscripts are stored in various locations around Malaysia. To form a unified collection of Malay manuscripts in Malaysia an Information System was developed to store the relevant information of the manuscripts. The information system is called a Union Catalogue of Malay Manuscripts. The objectives of the Union Catalogue are to provide an access to information pertaining to Malay manuscripts in Malaysia, an assistance for researchers to conduct research in manuscripts, and a new dimension to the field of big data in Islamic and Malay studies. The methodology used in the study is archival record analysis of the case study. As a result, an information system prototype was developed and enhanced for initial data storage. The completed prototype will be able to perform terminological analyses of Malay words, which are derived from Arabic words in the future.